Non invasive insulins: advanced insulin therapy over this decade - T. S. Rajeswari (Journal of Applied Pharmaceutical Science)
Frederick Banting and Charles Best extracted insulin from bovine pancreas in 1922, who received the Nobel Prize for their contribution in Medical field with John McLeod. Conventional insulin treatment involves replacement therapy, which involves the administration of insulin exogenously via subcutaneous route to mimic the pancreatic insulin secretion. Many people with types 1 and 2 diabetes over the world have used subcutaneous injections daily in order to control blood glucose level and/or to eradicate ketoacidosis which is really life threatening. Although, these injections avoid many complications, they became a source of inconvenience and lack of comfort. currently many other techniques have been investigated which resulted in delivering insulin other than subcutaneous route. These formulations are designed in such a way that they will overcome the inherent barriers of insulin uptake across the skin, gastro intestinal tract and mucous membrane. Various routes other than sub cutaneous which are under investigation for insulin therapy include oral, pulmonary, transdermal; nasal, buccal, ocular, rectal etc. Many approaches have been pursued in order to deliver insulin orally which include the use of absorption enhancers,inhibitors of proteases,inclusion of mucoadhesive components,buffers,micro and nano particles,liposomes,niosomes,microspheres,hydrogels, smart polymers etc.Over last few decades research is going on several non invasive routes for the delivery of insulin and many of them have stepped into pre clinical and clinical trials. Even products like Exubera ® and Oral-lyn™ were marketed after passing phase 3 clinical trials. Non invasive insulin delivery will definitely prove to be a boon to several patients who are currently depending on daily subcutaneous multiple injections.
Keywords: Subcutaneous, ketoacidosis, absorption enhancers, liposomes, microspheres, niosomes, hydrogels.